The strict metrical tradition : variations in the literary iambic pentameter from Sidney and Spenser to Matthew Arnold - Keppel-Jones, David, 1938- (McGill-Queen's University Press, 2001)
"A central issue in the recent surge of interest in metre on the part of theorists in different disciplines and practicing poets has been that of variations in the iambic pentameter. Keppel-Jones approaches this subject in a way that somewhat resembles Derek Attridge's, but is in fact very different." "The Strict Metrical Tradition focuses on a period of 275 years, during which iambic pentameter variations were conducted with special precision. Representative blocks of verse are chosen from major poets in original authoritative editions, and each variation is analysed on the basis of all cases of that variation. To give precision to certain of the principles, Keppel-Jones follows the linguist Bruce Hayes' definitions of boundaries between word-groups, but handles this material in such a way as to be understood by the general reader." "The practical result of this study is a new metre that allows Keppel-Jones to apply the principles of iambic variation to the anapest. His fascinating and original approach to iambic pentameter will appeal to scholars in the field and also to people with a general interest in poetry."--Jacket